Analisis Sistem Informasi Akuntansi dan Kinerja Pegawai terhadap Kualitas Laporan Keuangan pada Balai Pengembangan Kompetensi PUPR Wilayah I Medan - Batrisyia Alfaini Syabri; Kusmilawaty Kusmilawaty (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
ABSTRACTThe quality of financial reports is one the main factors used to show the performance of employees in a company. The purpose of this study is to determine whether accounting information systems and employess performance affect the quality of financia reports.This research uses qualitative methods by collecting theory with research result. The data collection technique used id interview. Analysis using data reduction, verification and conclusion techniques. The result of this study indicate that the accounting information system and employee performance at the Center for Competency Development of PUPR Region 1 Medan have an effect on the quality of financia reports.Keyword: Accounting Information System, Employee Performance, Quality of Financial Reports